Metabolic Syndrome and Risk of Upper Tract Urothelial Carcinoma: A Case-Control Study From Surveillance, Epidemiology and End Results-Medicare-Linked Database - Lu, Yi; Zhang, Wei; Fan, Shujun; Liang, Zhen; Li, Zhongjia; Tian, Jia; Kang, Jiaqi; Song, Yuxuan; Liu, Kang; Zhou, Kechong; Wang, Xiao; Yang, Yongjiao; et al. (Frontiers in Oncology, 2021)
Background: Metabolic syndrome (MetS) and its components are associated with increased risks of several cancers. However, the relationship between MetS and upper tract urothelial carcinoma (UTUC) has never been investigated before. Methods: We identified 3,785 UTUC cases aged over 65 years old within the Surveillance, Epidemiology and End Results-Medicare database between 2007 and 2016. For comparison, non-cancer controls (n=189,953) were selected from the 5% random sample of individuals residing within regions of SEER registries and matched with cases through diagnosis date and pseudo-diagnosis date. MetS and its components were all defined by using ICD-9-CM codes. Multivariate logistic regression models were conducted to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Time trends for MetS and its components were reported and we also performed dose-response effect analysis to test the concomitant effect of these components. The study was presented following the STROBE reporting checklist. Results: UTUC risk was associated with metabolic syndrome (NCEP-III: OR: 1.669, 95%CI: 1.550-1.792; IDF: OR: 1.924, 95%CI: 1.676-2.172) and its component factors: elevated waist circumference/central adiposity (OR: 1.872, 95%CI: 1.693-2.055), impaired fasting glucose (OR: 1.306, 95%CI: 1.133-1.480), high blood pressure (OR: 1.295, 95%CI: 1.239-1.353), high triglycerides (OR: 1.280, 95%CI: 1.222-1.341), and low high-density lipoprotein cholesterol (OR: 1.354, 95%CI: 1.118-1.592). Consistent associations could also be observed in the subgroup analyses by tumor stages, grades, and tumor size. Additionally, the rates of MetS increased over time in both UTUC and control cohort (NCEP-III criterion; EAPC: +18.1%, P <0.001; EAPC: +16.1%, P <0.001, respectively). A significantly gradual increase in UTUC rates could be seen as the No. of the MetS components increase (χ²=37.239, Ptrend=0.000). Conclusions: Among people aged over 65, MetS and its components were significant risk factors for UTUC with consistent associations in different tumor stages, grades, and tumor size. Even if a subject who did not meet the criteria for MetS had only one of the components, he (she) still had an elevated risk for UTUC. Strategies to control the epidemic of MetS and its components might contribute to a reduction in the UTUC burden. The findings should be considered tentative until ascertained by more researches.